2021
DOI: 10.1136/bmjopen-2020-043215
|View full text |Cite
|
Sign up to set email alerts
|

Scanxiety: a scoping review about scan-associated anxiety

Abstract: ObjectivesTo identify available literature on prevalence, severity and contributing factors of scan-associated anxiety (‘scanxiety’) and interventions to reduce it.DesignSystematic scoping review.Data sourcesOvid MEDLINE, Ovid EMBASE, Ovid PsycINFO, Ovid Cochrane Central Register of Controlled Trials, Scopus, EBSCO CINAHL and PubMed up to July 2020.Study selectionEligible studies recruited people having cancer-related non-invasive scans (including screening) and contained a quantitative assessment of scanxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…The term "scanxiety" was first coined in 2011 to reflect the fear, stress, and anxiety that accompanies scans and awaiting news of their results. 1 Although scanxiety can be considered a normal reaction to a repeated stressor, for many it is a considerably negative experience that impairs quality of life 2,3 and thus warrants research and clinical attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "scanxiety" was first coined in 2011 to reflect the fear, stress, and anxiety that accompanies scans and awaiting news of their results. 1 Although scanxiety can be considered a normal reaction to a repeated stressor, for many it is a considerably negative experience that impairs quality of life 2,3 and thus warrants research and clinical attention.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Most studies of scanxiety have used cross-sectional and retrospective methods to identify risk factors that are timeinvariant (e.g., lower education or a history of smoking) and confer risk for scanxiety over months or years. 3 Instead, EMA allows for dynamic capture of scanxiety across the anticipatory phase (the days or weeks leading up to the scan) and the recovery phase (the days or weeks following the scan) to identify factors that confer risk or protection for scanxiety over shorter periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…However, when experienced in excess, it can hamper the patient’s ability to deal with the stress they are exposed to ( Grilo et al, 2017 ). Anxiety caused by diagnostic procedures is recognized as a standard clinical concern in international cancer institutions ( Bui et al, 2021 , Coping with “Scanxiety” during and after Cancer Treatment, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative studies ( Bui et al, 2021 ) approached the experience of performing diagnostic procedures, showing that some patients felt fear in the preceding weeks. In some cases, these procedures are perceived by patients as unpleasant and causing claustrophobia ( Bui et al, 2021 , Evans et al, 2017 , Mathers et al, 2011 , Strand et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that follow-up scans (not specifically evaluated for brain imaging) may also have a negative impact on the QoL as these can induce feelings of scan-associated anxiety (scanxiety). 14 , 15 It is not known whether this also accounts for the follow-up with brain imaging.…”
Section: Introductionmentioning
confidence: 99%